Accuracy of Multimodality Fetal Imaging (US, MRI, and CT) for Congenital Musculoskeletal Anomalies - Roy U. Bisht; Mohan V. Belthur; Ian M. Singleton; Luis F. Goncalves (Children, 2023)
Background: Ultrasonography (US) is the first-line diagnostic tool used to assess fetal musculoskeletal (MSK) anomalies. Associated anomalies in other organ systems may benefit from evaluation via Magnetic Resonance Imaging (MRI). In this study, we compared the diagnostic accuracy of US and MRI to diagnose fetal MSK (primary objective) and non-MSK anomalies (secondary objective). We describe additional findings by low-dose computerized tomography (CT) in two cases incompletely characterized via US and MRI. Materials and Methods: This was an IRB-approved retrospective study of consecutive patients with suspected fetal MSK anomalies examined between December 2015 and June 2020. We compared individual MSK and non-MSK anomalies identified via US, MRI, and CT with postnatal outcomes. Sensitivity and specificity for US and MRI were calculated and compared. Results: A total of 31 patients with 112 MSK and 43 non-MSK anomalies were included. The sensitivity of MRI and US for MSK anomalies was not significantly different (76.6% vs. 61.3%, p = 0.3). Low-dose CT identified eight additional skeletal anomalies. MRI diagnosed a higher number of non-MSK anomalies compared to US (81.4% vs. 37.2%, p < 0.05). Conclusions: Fetal MRI and US have comparable sensitivity for MSK anomalies. In selected cases, low-dose CT may provide additional information. Fetal MRI detected a larger number of non-MSK anomalies in other organ systems compared to US. Multimodality imaging combining all the information provided by MRI, US, and CT, if necessary, ultimately achieved a sensitivity of 89.2% (95% CI: 83.4% to 95.0%) for the diagnosis of musculoskeletal anomalies and 81.4% for additional anomalies in other organs and systems.